Melting Antarctic Sea Ice Is Yielding Adverse Effects on a Short-Lived Squid Species in the Antarctic Adjacent Waters - Liu, Hewei; Yu, Wei; Chen, Xinjun (Frontiers in Marine Science, 2022)
Variation in Antarctic sea ice strongly impacts marine ecosystem and fisheries. In this study, Antarctic sea ice extent (SIE) was used as an indicator to characterize the Antarctic sea ice variation, and its impact on habitat pattern of Argentine shortfin squid Illex argentinus, a climate-sensitive squid species extensively distributed in the Antarctic adjacent waters, was assessed using the habitat suitability index (HSI) modeling approach. The HSI model was established on the basis of the fisheries data and sea water temperature at critical depths of 50, 100, and 200 m in the high-sea fishing ground of the Southwest Atlantic Ocean from January to April during 1979–2017. Results showed that a significantly positive correlation was found between SIE and the areas of suitable habitat of I. argentinus. The years with high and low SIE were selected and divided into two groups from 1979 to 2017. Generally, the year group with high SIE yielded warmer sea water temperature at different depths; consequently, the suitable habitats enlarged; and the optimal temperature isotherm for I. argentinus moved northward, resulting in a northward movement of suitable habitats. On the contrary, the situation in the year group with low SIE was opposite. Our findings suggest that the melting Antarctic sea ice is yielding adverse effects on I. argentinus habitat in the Southwest Atlantic Ocean by affecting the sea water temperature at three critical depths.